2022
DOI: 10.3390/su14159170
|View full text |Cite
|
Sign up to set email alerts
|

State-Level Urban Agglomeration and Enterprise Innovation: A Quasi-Natural Experiment

Abstract: Based on the data of listed enterprises in China from 2007 to 2019, this study uses the quasi-natural experiment method (staggered DID) to explore the actual impact of the establishment of state-level urban agglomeration on the innovation activities of enterprises and the heterogeneous impact caused by regional differences. It is found that state-level urban agglomerations play the role of “incubator” for enterprise innovation, and the establishment of urban agglomerations can not only effectively encourage en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Zhao et al . 21 analyzed the impact of establishing urban agglomerations on innovation by utilizing data from Chinese listed companies and employing quasi-natural experiment methods. They found that the establishment of national-level urban agglomerations encouraged enterprises to increase R&D expenditure and enhances their innovation output.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al . 21 analyzed the impact of establishing urban agglomerations on innovation by utilizing data from Chinese listed companies and employing quasi-natural experiment methods. They found that the establishment of national-level urban agglomerations encouraged enterprises to increase R&D expenditure and enhances their innovation output.…”
Section: Introductionmentioning
confidence: 99%